A science for verbal art: Elizabeth Gaskell's contribution to a critique of political economy. (November 2018) - Li, Fang; Kellogg, David
Abstract: The two central arguments of this paper are symmetrical: language science is a science for verbal art, and Elizabeth Gaskell's verbal art offers a way of understanding the historical method pioneered by Marx and using it to develop language science in turn. The argument unfolds on three different timescales, examining the logogenetic development of one work, the ontogenetic development of one writer, and the sociogenetic development of one genre, namely the nineteenth century social-realist novel. Taking a logogenetic view, we use a Hallidayan linguistic framework to show how Elizabeth Gaskell's treatment of inter-class dialogue differs from that of the man who was probably her first Marxist critic—Marx himself. Taking an ontogenetic view, we use Hasan's distinction between theme, verbalization, and symbolic articulation to compare an earlier industrial novel by Gaskell with a later one. Taking a sociogenetic view, we argue that Gaskell's role in the development of the novel genre may also be understood through a comparative linguistic contrast between her work and previous and succeeding literary genres. Highlights: Shows, by comparison of word selection, Hasan's distinction between literary and literature text. Shows the ontogenetic development of Gaskell as author by demonstrating how her two industrial novels differ in Theme and Symbolic Articulation. Shows the generic antecedents and successors of the industrial novels by applying Marx's historical method.